Диалоговые технологии - основа развития творческого потенциала учащихся на уроках математики в начальной школе - Ворог, Л. А. (My University, 2016)
The article is devoted to the pedagogy of reflective activity which demands another structure of the role model for both participants as for a teacher so for a pupil. The content of the text includes the opportunities of using interactive technologies which help to develop the creative potential of young learners through dialogue (discussion, dispute) on the Mathematics lesson. The article shows how to create the situations for interaction for all stages of the lesson using didactic games. The key conclusion of the article is the dialogue form of the lesson helps learners to be active in the process of getting knowledge during the whole lesson
Keywords: nteractive technology \ situation; monologue; speech; dialogue; verbal and semantic level; questions; interaction